1974 Annual Report of the Appalachian Regional Commission - Appalachian Regional Commission, Washington, DC.; Kendrick, Elise F.; Appalachian Regional Commission, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Created via the Regional Development Act of 1965, the Appalachian Regional Commission documents its contributions to Appalachian socioeconomic development in this 1974 annual report. General areas of concern are identified as: (1) extension of public services to outlying areas; (2) improvement of public service quality and quantity; (3) promotion of responsible energy development; and (4) extension of local developmental responsibilities. Detailed data are provided for the following specific areas of concern: The Region and the Appalachian Experiment; The Federal-State-Local Partnership; The New Subregions; Population, Income, and Employment; Finances; Transportation; Supplemental Grants; Health; Child Development; Education; Community Facilities and Housing; Energy, Environment, and Natural Resources; and Research and Planning. Among some of the more noteworthy accomplishments cited for 1974 are: a shift from outmigration to inmigration; completion of 150 corridor miles of highway construction; acquisition of funding for comprehensive health services in 389 counties; operation of 233 child development projects and vocational education facilities with a capacity for 310,000 students; and appropriation of $37,000,000 for supplemental grants to vocational education schools, sewage treatment plants, colleges, libraries, and other public facilities. (JC)
ERIC Note: For related documents, see ED 093 512.
Microfiche.
Keywords: Annual Reports; Child Development; Developmental Programs; Economic Development; Education; Employment Patterns; Federal State Relationship; Financial Support; Health; Housing; Human Services; Income; Natural Resources; Planning; Population Trends; Public Facilities; Research; Rural Areas; Tables (Data); Transportation; Appalachia; Appalachian Regional Commission DC; Reports, Descriptive